ACCOUNTING FOR FIXED ASSETS: A NEW PERSPECTIVE. - Hirschk, A. Jay (The Accounting Review, 1964)
It is true, of course, that accountants have been concerned with the problem area of fixed assets for a long time. Yet, many significant questions are unresolved. This article suggests a new look and solution to certain of these problems. This is done by extending fundamental ideas of financial accounting to areas now ignored. The suggested extension of accounting reflects the managerial function of planning and controlling plant and equipment assets. It does this by developing the essential characteristics and the unique contribution to the firm of plant and equipment assets over their lives. It is important for the reader to realize that the suggestion is not a plea for external reporting of capital budgets as they now exist. Instead, the impact of this idea has a bearing on conventional accounting practices. The general role of managers and financial accounting relative to fixed assets will be reviewed initially in this article. The overall management activity of planning and control will be expressed in terms of an asset's life cycle as outlined below.